2019
DOI: 10.1016/j.ijantimicag.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antivirulence activities of auranofin against Clostridium difficile

Abstract: Clostridium difficile is a deadly, opportunistic bacterial pathogen. In the last two decades, C. difficile infections (CDIs) have become a national concern due to the emergence of hypervirulent mutants armed with a higher capability of producing toxins and spores. This has resulted in an increased number of infections and death associated with CDI. The scarcity of anticlostridial drugs has led to unsatisfactory cure rates, elevated recurrence rates and permitted enhanced colonization with other drug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
7
55
0
Order By: Relevance
“…Investigation into the mechanisms of AXPN revealed that drug administration was associated with increased neutrophil recruitment that contributed to an elevated IL-33 response, which was critical for pathogen control. Our findings paralleled recent observations that several FDAapproved drugs, including auranofin, an antirheumatic, and mistroprostol, a prostaglandin analog, were effective against experimental CDI (39)(40)(41). However, important differences in the modes of action exist between these drugs.…”
Section: Discussionsupporting
confidence: 88%
“…Investigation into the mechanisms of AXPN revealed that drug administration was associated with increased neutrophil recruitment that contributed to an elevated IL-33 response, which was critical for pathogen control. Our findings paralleled recent observations that several FDAapproved drugs, including auranofin, an antirheumatic, and mistroprostol, a prostaglandin analog, were effective against experimental CDI (39)(40)(41). However, important differences in the modes of action exist between these drugs.…”
Section: Discussionsupporting
confidence: 88%
“…Auranofin is an FDA-approved, gold-containing, drug used to treat rheumatoid arthritis. Previous studies on auranofin have reported that the drug possesses potent antibacterial activity against clinically-pertinent pathogens including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Clostridioides difficile [15][16][17][18][19][20] . However, no reports have investigated the effect of auranofin against N. gonorrhoeae.…”
mentioning
confidence: 99%
“…toxin inhibition assay. Based on their proposed mechanism of action, mithramycin A 56 and aureomycin 57 , were investigated to evaluate their effects on toxin production by C. difficile ATCC BAA 1870, with slight modifications 58 . Briefly, C. difficile strain ATCC BAA 1870 was cultured on BHIS agar plates and incubated anaerobically for 48 hours at 37 °C.…”
Section: Methodsmentioning
confidence: 99%